Identification of coal seams suitability for carbon dioxide sequestration with enhanced coalbed methane recovery: a case study in South Sumatera Basin, Indonesia - Pratama, E. (Springer Verlag, 2018)
Sequestering carbon dioxide (CO2) with enhanced coalbed methane recovery (ECBM) is a promising clean coal technology in Indonesia, which can reduce CO2 emissions and potentially lower-cost alternative for fulfilling of future Indonesiaâs gas demand. Coal seams in South Sumatera Basin, Indonesia, are well placed to take advantage of CO2 sequestration based on economical and regulatory criteria. From technical criteria assessment, there are very limited studies undertaken in this area, especially for identification of coal seams suitability for CO2-ECBM in South Sumatera Basin. This study has therefore aimed to propose the technical criteria of coal seams suitability for CO2-ECBM recovery as well as predicting CO2 storage capacity by developing a novel numerical model based on the characteristics of coal seams in South Sumatera Basin. The comparison of primary and CO2-ECBM recovery was analysed by performing production forecasting for 30Â year of simulation. A sensitivity study was then conducted in order to examine the performance of CO2-ECBM under the influences of permeability, a determining factor in the viability of a CO2 storage in coal seams. A simplified method for estimating CO2 storage capacity in coal seams has been proposed which was validated with the novel numerical model through parametric studies. From this study, one can screen the suitable coal seams for CO2 storage with enhanced coalbed methane recovery and can quickly quantify the CO2 storage capacity in the coal seams with general available data. Â© 2017, Springer-Verlag GmbH Germany.